Arterial Stiffening in Western Diet-Fed Mice Is Associated with Increased Vascular Elastin, Transforming Growth Factor-β, and Plasma Neuraminidase - Foote, Christopher A.; Castorena-Gonzalez, Jorge A.; Ramirez-Perez, Francisco I.; Jia, Guanghong; Hill, Michael A.; Reyes-Aldasoro, Constantino C.; Sowers, James R.; Martinez-Lemus, Luis A. (Frontiers in Physiology, 2016)
Consumption of excess fat and carbohydrate (Western diet, WD) is associated with alterations in the structural characteristics of blood vessels. This vascular remodeling contributes to the development of cardiovascular disease, particularly as it affects conduit and resistance arteries. Vascular remodeling is often associated with changes in the elastin-rich internal elastic lamina (IEL) and the activation of transforming growth factor (TGF)-β. In addition, obesity and type II diabetes have been associated with increased serum neuraminidase, an enzyme known to increase TGF- β cellular output. Therefore, we hypothesized that WD-feeding would induce structural modifications to the IEL of mesenteric resistance arteries in mice, and that these changes would be associated with increased levels of circulating neuraminidase and the up-regulation of elastin and TGF-β in the arterial wall. To test this hypothesis, a WD, high in fat and sugar, was used to induce obesity in mice, and the effect of this diet on the structure of mesenteric resistance arteries was investigated. 4-week old, post-weaning mice were fed either a normal diet (ND) or WD for 16 weeks. Mechanically, arteries from WD-fed mice were stiffer and less distensible, with marginally increased wall stress for a given strain, and a significantly increased Young’s modulus of elasticity. Structurally, the wall cross-sectional area and the number of fenestrae found in the internal elastic lamina (IEL) of mesenteric arteries from mice fed a WD were significantly smaller than those of arteries from the ND-fed mice. There was also a significant increase in the volume of elastin, but not collagen in arteries from the WD cohort. Plasma levels of neuraminidase and the amount of TGF- in mesenteric arteries were elevated in mice fed a WD, while ex vivo, cultured vascular smooth muscle cells exposed to neuraminidase secreted greater amounts of tropoelastin and TGF- than those exposed to vehicle. These data suggest that consumption of a diet high in fat and sugar causes stiffening of the vascular wall in resistance arteries through a process that may involve increased neuraminidase and TGF- activity, elevated production of elastin, and a reduction in the size and number of fenestrae in the arterial IEL.